Posttranscriptional deregulation of Src due to aberrant miR34a and miR203 contributes to gastric cancer development - Qiang Hao (BMB Reports, 2013)
Gastric cancer remains the main cause of cancer death allaround the world, and upregulated activation of thenonreceptor tyrosine kinase c-SRC (SRC) is a key player in thedevelopment. In this study, we found that expression of Src isalso increased in clinical gastric cancer samples, with theprotein level increased more significantly than that at the RNAlevel. Further study revealed that miR34a and miR203, twotumor suppressive miRNAs, inversely correlate with theexpression of Src. Restoration of miR34a and miR203 decreasedSrc expression in gastric cancer cell lines, which in turninhibited cell growth and cell migration. In summary, ourstudy here revealed that posttranscriptional regulation of Srccontributes to the deregulated cell growth and metastasis ingastric cancer, and targeting Src by miR34a or miR203 mimicswould be a promising strategy in therapy. [BMB Reports 2013;46(6): 316-321]